Faktor-Faktor yang Berhubungan dengan Stres Kerja pada Pegawai Negeri Sipil Badan Penanggulangan Bencana Daerah (BPBD) Kota Semarang - Kartika Wahyuning Purnama; Ida Wahyuni; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Work stress is an emotional condition that occurs because of the gap between the level of demand and the ability to cope with stress received due to demands at work. Any work have potential danger of work stress including working as a civil servant in the Regional Disaster Management Agency. The purpose of this research was to analyze factors that related to work stress. The design of this research was explanatory research with cross-sectional approach. Population in this research was 48 civil servants of BPBD Kota Semarang. Questionnaire was used as an instrument in this research. Measurement of work stress was assessed by GHQ-12 questionnaire. Statistical analysis was used chi-square test. The results of the research showed that there was a relation between work period (p=0.015), personality (p=0.008), individual role in organization (p=0.041), and work relations (p=0.034) with work stress, while there was no relation between age (p=0.184), task demands (p=0.109), career development (p=0.073) and organizational structure and climate (p=0.178) with work stress. Researchers suggest giving socialization to employees about the risks of work stress at work, socialization clarity of responsibility, stretching while working, sharing about work issues with colleagues and organizing recreational or outbound activities on days off to reduce employee stress problems.